Rare association of Turner syndrome and Mayer-Rokitansky-Kuster Hauser syndrome - Ndiade, Amadou; Thiam, Mbaye; Dia, Sérigne A. M.; Sy, Mama (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Turner syndrome and Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome is a rare association. The incidences of Turner and MRKH syndromes are estimated at 1/2000 and 1/4500 female births respectively. This is a 23-year-old patient, born of a consanguineous marriage, who was referred to us for exploration of primary amenorrhoea. The karyotype, performed three times, from peripheral blood lymphocytes was 45X0. The diagnosis of Turner syndrome associated with MRKH syndrome was retained.